Early quantification of reliability for a safety critical and control system: a case study of reactor core cooling system - Kumar, Vinay; Gupta, Suraj; Kumar Tripathi, Anil (International Journal of Engineering and Technology, 2018)
Using Probabilistic Reliability analysis for Quantifying reliability of a system is already a common practice in Reliability Engineering community. This method plays an important role in analyzing reliability of nuclear plants and its various components. In Nuclear Power Plants Reactor Core Cooling System is a component of prime importance as its breakdown can disrupt Cooling System of power plant. In this paper, we present a framework for early quantification of Reliability and illustrated with a Safety Critical and Control System as case study which runs in a Nuclear Power Plant.Â Â